VD_FINDINFO Plainte / 2013 / 35 vom 19. November 2013 - VD Tribunal cantonal (2013)
PLAINTELP, GAGE IMMOBILIER, POURSUITE EN RÉALISATION DE GAGE, CONDITIONS DES ENCHÈRES | 126 LP, 133 LP, 141 al. 1 LP, 17 LP, 28 LVLP, 45 ORFI